(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay recalls the long debate on the evolution of the Italian health care service, with a particular focus on its origins and its founding principles. These are identified as milestones of right to healthcare and serve as a basis for a discussion on remedies and malfunctions highlighted during the pandemic emergency.